DISASTER PREPAREDNESS TRAINING FOR STUDENTS OF MI MUHAMMADIYAH BLEMBEM GUNUNGKIDUL - Restu Faizah; Sri Atmaja P Rosyidi; Bunsa Jondan Satriawan; Anisa Fitriani La Kasim (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
Madrasah Ibtidaiyah (MI) Muhammadiyah Blembem is an elementary school located in Candirejo Village, Kapanewon Semin, Gunungkidul Regency. The school is accredited by B, with a total of 93 students. In 2022 there was a landslide disaster in a location close to the school, and it caused casualties and the loss of several houses due to being buried. Several students living in the affected areas also felt the impact of the landslide disaster which caused trauma. Therefore, students need a good understanding of the threat of disasters at school locations and the preparedness they must have. This service community activity intends to provide an understanding of disaster to students through workshops and games. After participating in this disaster workshop, students are expected to know the condition of the school and the disaster threats that exist in the school environment and have good preparedness if a disaster does occur in the future. The disaster workshop activity was held on March 4, 2023, at the MI Muhammadiyah Blembem location and was attended by 39 students from classes 3, 4, and 5. Participants are involved in games, singing, and watching videos to provide a good understanding of disaster preparedness. Based on the pretest and post-test questionnaires, the results obtained were 10 - 80% of students felt they had gained a new understanding of the disaster. This understanding is expected to increase student preparedness in dealing with disasters and eliminate trauma